Schädlinge an Arzneidrogen und Gewürzen in Hamburg. - Weidner, Herbert (Contributions to Entomology = Beiträge zur Entomologie, 1963)
72 simples, drugs, and spices infested by insects and mites are enumerated. The most frequent insects, Plodia interpunctella (Hbn.), Oryzaephilus mercator (Fauv.), Lasioderma serricorne (F.), and Tribolium castaneum (Herbst), are imported from tropical or warm countries. In countries with a temperate climate Ephestia elutella (Hbn.) and Stegobium paniceum (L.) are most important. They are therefore also frequent pests in German chemist's shops. It is the effect partly of unfavorable climate and partly of successful control, that other pests in shops are rare. More informations about pests of Semen Myristicae, Flores Aurantii, and Fructus Cassiae fistulae are given.